Modified staging system for gastric neuroendocrine carcinoma based on American Joint Committee on Cancer and European Neuroendocrine Tumor Society systems. Issue 3 (23rd January 2020) - Lu, J.; Zhao, Y. J.; Zhou, Y.; He, Q.; Tian, Y.; Hao, H.; Qiu, X.; Jiang, L.; Zhao, G.; Huang, C.‐M.; ,
Abstract : Background: The prognostic values of the AJCC staging system for gastric cancer (GC‐AJCC), the AJCC staging system for gastric neuroendocrine tumours (NET‐AJCC) and the European Neuroendocrine Tumor Society (ENETS) system for gastric neuroendocrine carcinoma and mixed adenoneuroendocrine carcinoma (MA)NEC remain controversial. Methods: Data on patients with (MA)NEC from 21 centres in China were analysed. Different staging systems were evaluated by performing Kaplan–Meier survival analysis and calculating the concordance index (C‐index) and Akaike information criterion (AIC). Based on three existing systems, a modified staging system (mTNM) was developed. Results: A total of 871 patients were included. In the GC‐AJCC system, an overlap was noticed for pT2 and pT3 categories. Patients with stage IIIC disease had a similar prognosis to those with stage IV disease. The pT categories of the NET‐AJCC system had a lower C‐index and higher AIC than those of the other systems. In the ENETS system, there was a low proportion (0·2 per cent) of patients with stage IIIA and a high proportion (67·6 per cent) of stage IIIB disease. The mTNM system adopted the NET‐AJCC pT and GC‐AJCC pN and pM definitions, and was developed based on the ENETS stage definitions. The proportion of patients in each stage was better distributed and the mTNM system showed improved prognostic performance in predicting overall and disease‐free survival. Conclusion: The mTNM system offers more accurate prognostic value for gastric (MA)NEC than the AJCC or ENETS staging systems. Abstract : The prognostic value of different staging systems in patients with gastric neuroendocrine and mixed adenoneuroendocrine carcinoma (MA)NEC remains controversial. A modified staging system was established, which was found to be more suitable for gastric (MA)NEC than AJCC systems and European Neuroendocrine Tumor Society staging systems. However, this needs to be further verified by external data.